The Possibility of Oversupply with External Economies - Robin Boadway (Queen's University, Department of Economics, 1971)
Until fairly recently, the Pigovian position that activities generating unpriced external economies would be undersupplied was universally accepted. It rested on the simple assertion that marginal social benefits exceeded marginal private benefits of the activity, and that, by equating the latter to the price,the marginal social benefit would exceed the price and the activity should be expanded. As a result in this paper, we have analysed the conditions under which oversupply could occur in the presence of external economies. In doing so, we have shown Baumol's analysis to be based upon a misleading definition of "externality". Furthermore,we have shown that the results arrived at by Vincent were faulty for several reasons. Also, the correct partial method is shown, but even it gives incorrect results. What is required is a simultaneous equation method to determine changes in a and b,such as is given in this paper.
Keywords: 330